Fine needle aspiration cytology of breast lumps: how reliable is it? A correlative study with histopathology - Agrawal, Sakshi; Agrawal, Sumedh; Gadre, A. S.; Dravid, N. V. (International Journal of Research in Medical Sciences, 2025)
Background: Breast carcinoma is one of the most common malignancies in women. Palpable breast lesions are one of the commonest presentations in general and surgical practice. To study the spectrum of benign and malignant breast lesions and the efficacy of FNAC as a diagnostic tool by correlating with histopathological findings. Methods: The present study was carried out among 250 patients who presented to ACPM medical college and hospital during a 5-year period from January 2018 to January 2023. All cases that presented with a palpable breast lump were evaluated with FNAC and the lesions were categorised as C1-C5 as per National Health Service Breast screening programme (NHSBSP) reporting criteria. Every patient subjected to FNAC with an adequate result, underwent a definitive surgical procedure. All specimens so obtained were subjected to histopathology. The results thus obtained were matched with those of FNAC and a correlation was sought based on statistical tests. In 243 cases cytohistopathological correlation was obtained. Results: A total of 250 cases was studied which included 170 benign cases (68%), 52 malignant cases (20.8%), 21 proliferative lesions with atypia (8.4%) and 7 inadequate aspirates (2.8%). The diagnostic accuracy of FNAC in this study was 98.77%. Conclusions: Aspiration cytology can be done as a first line procedure but cannot be considered as a substitute for histopathology.